Trajnostno poročanje gospodarskih družb v Republiki Sloveniji - Djokić, Danila (Podjetje in delo, 2020)
The article summarises the development of sustainable reporting in the EU and analyses the statements on non-financial operations in the Republic of Slovenia, as they are implemented in practice after the amendment of Article 70c of the Companies Act (ZGD-1J). The latest analysis of TRP SI 2018 in the Republic of Slovenia is presented, which draws attention to sufficient results of sustainable reporting and encourages the improvement of the situation in the future.
Keywords: družbena odgovornost; izjava o nefinančnem poslovanju; nefinančno poročanje; non-financial reporting; preglednost; social responsibility; statement on non-financial operations; sustainable development; sustainable report; sustainable reporting; trajnostni razvoj; trajnostno poročanje; trajnostno poročilo; transparency